PROBLEMATIKA PENGGUNAAN DESAIN INDUSTRI PADA ALAT MUSIK TRADISIONAL - Budi Kurniawan (LP2M ISBI Bandung, 2017)
Industrial Design Act No. 31 of 2000 provides protectiontoany ornamental or aesthetic aspect of an article. Hence, it gives widestopportunity to people to createa creativedesign. On the other side, Traditional MusicInstrument which is partoffolkloreortraditional cultural expression(TCE) insome way still give an opportunity to anyone also to add an element and or make new design inherenttoinstruments.A mix betweenpublicowned rightsof TraditionalMusic Instrument and theprivaterightofIndustrial Designarisenew problemin legal sense including to define an exact definition ofa